Perils, Pitfalls and Reflexivity in Qualitative Research in Education - Edited by Fauzia Shamim; Rashida Qureshi (Karachi Oxford University Press, 2010)
This exciting new collection of critical reflections on conducting qualitative research gives a unique insight into the experiences of researchers working in countries in the South Asia. Perils, Pitfalls and Reflexivity in Qualitative Research in Education explores how "Western" theoretical concepts and research approaches developed in the North can be adapted to respond to the developing country communities. The firsthand accounts enhance readers understanding of what it means to conduct research in developing country contexts, and allows readers to interrogate their own ethical and methodological assumptions in relation to these reflexive discussions on research emerging from and within contrasting cultural contexts.
Include Appendix.
Keywords: Pakistan -- Research in Education -- Qualitative Research in Pakistan